Pemeriksaan Protein Urine pada Ibu Hamil Trimester III di RSIA Artha Mahinrus Medan Perjuangan - SYAHNIMAN, SYAHNIMAN (Journal of Engineering and Information Technology for Community Service, 2024)
Preeclampsia is a disease of pregnancy. Preeclampsia is the presence of hypertension accompanied by edema due to pregnancy and the most important sign is the presence of proteinuria. Proteinuria occurs more slowly in early pregnancy until it finally appears at the end of the pregnancy trimester. Urine Protein Examination in Trimester III Pregnant Women at RSIA Artha Mahinrus, This study aims to determine the results of urine protein in third trimester pregnant women at RSIA Artha Mahinrus Medan Perjuangan based on age and urine protein results. This research uses descriptive method. The study sample was 38 third trimester pregnant women who were taken using the slovin formula with random sampling technique. Examination of proteinuria using the dipstick method which is read with a Dirui H-100 urine analyzer. The results showed as many as 61% positive urine protein, and 39% negative urine protein in third trimester pregnant women. It is recommended for medical staff to encourage pregnant women to do laboratory tests.